Effects of high-temperature operating conditions on the through-plane gas permeability of gas diffusion layers used in PEFCs / Raja Muhammad Aslam Raja Arif - Raja Arif, Raja Muhammad Aslam (Smart Manufacturing Research Institute (SMRI), 2021)
In order to simulate the effects of high-temperature operating conditions on the through-plane gas permeability of gas diffusion layers (GDLs) used in polymer electrolyte fuel cells, uncoated and coated GDLs were heated at various temperatures (i.e. 200, 500 and 800 °C). The results show that the through-plane gas permeability of the uncoated GDLs generally increases after higher temperature treatment. However, the coated GDL displays a different trend: the through-plane gas permeability increases with increasing temperature treatment to 200 and 500 °C, but then decreases after heat treatment at 800 and 1000 °C. With the assistance of SEM images, the above results are discussed.